Analysis and conservation of a Bronze Age linen textile from Suffolk, UK - Harrison, Anna; Cartwright, Caroline; Harris, Susanna; Shearman, Fleur; Wilkin, Neil (Archaeological Textiles Review, 2023)
A rare Bronze Age linen textile was found inside a socketed axe, part of a bronze age hoard dating to circa 800 BCE, discovered in Somerleyton, Suffolk, in the 1920s. The recent loan of the objects from the hoard provided the opportunity for a collaborative study of the fragmentary textile and its original context and significance. Scanning electron microscopy and energy-dispersive X-ray spectroscopy were undertaken to update and inform interpretations of its condition, character and function. The remounting of the textile was necessary for display. The conservation challenges this raised, and the solutions found, are detailed here. The wider study of the metalwork associated with the hoard and of the current state of knowledge regarding Bronze Age textiles in Britain allowed for several hypotheses to be put forward about the textile’s functional significance in efficient hafting techniques and its potential votive symbolism. The Somerleyton textile serves as a reminder of the need to contextualise Bronze Age metalwork within wider networks of (organic) materials and the potential of older collections to provide new insights.